Winter annual forage mass–nutritive value trade‐offs are affected by harvest timing. Issue 2 (4th August 2021) - Billman, Eric D.; de Souza, Igor A.; Smith, Richard G.; Soder, Kathy J.; Warren, Nicholas; Teixeira, Fabio A.; Brito, Andre F.
Abstract: Annual cool‐season forage crops could fill the gaps in spring forage availability that are typical in perennial pastures in the northeastern United States. Despite their potential as supplemental forages, few studies have examined the productivity–quality tradeoffs of annual forages grown as monocultures or mixtures. This study compared five species of winter annual forages grown as monocultures and mixtures for forage mass production and nutritive value across three harvest timepoints. Beginning in fall 2015, plots were planted in monocultures of cereal rye ( Secale cereale L.), barley ( Hordeum vulgare L.), triticale [ ×Triticosecale Wittm. ex A. Camus ( Secale × Triticum )], wheat ( Triticum aestivum L.), and hairy vetch ( Vicia villosa Roth), as well as a mix of all five species. Samples were taken on 1, 7, and 14 June 2016, and on 3, 10, and 17 May 2017 to determine forage mass, nutritive value in the second year, and tradeoffs between biomass and nutritive value. The mixture's forage mass always ranked similarly to the best performing monoculture treatments. All monocultures except hairy vetch had increased forage mass at later harvests. In vitro digestibility of neutral detergent fiber was lower in later harvests. Triticale consistently had the greatest forage mass. Barley had greater energy and lower fiber concentrations than the other species. The results of this study suggest that triticale and barley have the most potential for supplementing spring perennial forage production. Core Ideas: Winter annual forages differ in their comparative forage mass and nutritive value. Cereal rye and triticale had the greatest forage mass but poorest nutritive value. Barley had low forage mass but greater crude protein and less fiber. Hairy vetch production was poor.